(untitled) (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2025)
The book Artificial and Emotional Intelligence for Employee by Mishra et al. (2025) offers an extensive, integrative analysis of how artificial intelligence (AI) and emotional intelligence (EI) intersect within human resource management (HRM) and employee engagement. Published by Intellectuals’ Book Palace, this volume thoughtfully addresses the rapidly evolving digital workplace, highlighting how technological innovation and emotional competencies collectively redefine modern workforce management. In today’s complex and dynamic world, particularly in the Nepalese context, HR professionals face unprecedented challenges. The digital transformation, shifting workforce expectations, and the demand for agility compel organizations to rethink their traditional HR models. The authors place this scenario at the forefront, laying the foundation for understanding how AI and EI can be harnessed synergistically to navigate these disruptions and unlock new potentials.